Characterization and cytotoxicity studies of thiol‐modified polystyrene microbeads doped with [Mo6X8(NO3)6]2– (X = Cl, Br, I)1. (11th January 2016) - Vorotnikova, Natalya A.; Efremova, Olga A.; Tsygankova, Alphiya R.; Brylev, Konstantin A.; Edeleva, Mariya V.; Kurskaya, Olga. G.; Sutherland, Andrew J.; Shestopalov, Alexandr M.; Mironov, Yuri V.; Shestopalov, Michael A.
Abstract : Halide octahedral molybdenum clusters [Mo6 X8 L6 ] n– possess luminescence properties that are highly promising for biological applications. These properties are rather dependent on the nature of both the inner ligands X (i.e. Cl, Br, or I) and the apical organic or inorganic ligands L. Herein, the luminescence properties and the toxicity of thiol‐modified polystyrene microbeads (PS‐SH) doped with [Mo6 X8 (NO3 )6 ] 2– (X = Cl, Br, I) were studied and evaluated using human epidermoid larynx carcinoma (Hep2) cell cultures. According to our data, the photoluminescence quantum yield of Mo6 I8 @PS‐SH is significantly higher (0.04) than that of Mo6 Cl8 @PS‐SH (<0.005) and Mo6 Br8 @PS‐SH (<0.005). Treatment of Hep2 cells with Mo6 X8 @PS‐SH showed that all three types of doped microbeads had no significant effect on the viability and proliferation of the cells. Copyright © 2016 John Wiley & Sons, Ltd.